Challenges in Singapore Aquaculture and Possible Solutions - Shubha Vij; Yeng Sheng Lee; Kathiresan Purushothaman; Dean Jerry (Aquaculture Journal)
Singapore’s aquaculture sector is critical to achieving the nation’s ‘30 by 30’ food security goal, which aims to produce 30% of its nutritional needs locally by 2030. However, the sector faces several significant challenges. Limited land and water resources, high operational costs, disease outbreaks, reliance on imported seedstock, and environmental impact are among the key issues. Additionally, the industry struggles with a shortage of skilled manpower and high dependency on foreign labour. This study explores these challenges in detail and suggests potential solutions to enhance the sustainability and productivity of Singapore’s aquaculture. Innovative farming techniques such as recirculating aquaculture systems (RASs) and vertical farming, advanced water quality management, and the adoption of renewable energy sources are recommended to address space and cost constraints. Developing local breeding facilities, enhancing education and training programs, and adopting sustainable practices are also crucial. The establishment of a national hatchery and increased investment in research and development (R&D) are essential for long-term growth. By implementing these strategies, Singapore can overcome the challenges in its aquaculture sector and ensure a sustainable future for local food production.